Respuesta :
The answer you are looking for is "-Cos(x)-2=Y)
This is because converting Cos to a negative value causes all values to change integers in terms of Cos, and (-2) vertically shifts the equation 2 values downward.
-I hope this is the answer you are looking for please feel free to post your questions here on brainly in the future.
This is because converting Cos to a negative value causes all values to change integers in terms of Cos, and (-2) vertically shifts the equation 2 values downward.
-I hope this is the answer you are looking for please feel free to post your questions here on brainly in the future.
Answer:
The required equation is [tex]y=-\cos (x)-2[/tex]
Step-by-step explanation:
Given : Equation [tex]y=\cos x[/tex]
To find : The equation represents the graph of [tex]y=\cos x[/tex] flipped across the x - axis then shifted vertically down by 2 units.
Solution :
The equation is [tex]y=\cos x[/tex]
- The equation is flipped across the x - axis.
The reflection of the point (x,y) across the x-axis is the point (x,-y).
f(x,y)→f(x,-y)
[tex]-y=\cos x[/tex]
[tex]y=-\cos x[/tex]
- Shifted vertically down by 2 units.
Shifted downward means function is shifted by a unit .
f(x)→f(x)-b , function is shifting downwards by b unit.
[tex]y=-\cos (x)-2[/tex]
Therefore, The required equation is [tex]y=-\cos (x)-2[/tex]